Improving the predictability of real economic activity and asset returns with forward variances inferred from option portfolios - Bakshi, Gurdip; Panayotov, George; Skoulakis, Georgios (Journal of Financial Economics, 2011)
This paper presents an option positioning that allows us to infer forward variances from option portfolios. The forward variances we construct from equity index options help to predict (i) growth in measures of real economic activity, (ii) Treasury bill returns, (iii) stock market returns, and (iv) changes in variance swap rates. Our yardstick for measuring predictive ability is both individual and joint parameter statistical significance within a market, as well as across a set of markets.